To the 80-th Anniversary of Lidiya S. Pronina - article Editorial (Проблемы особо опасных инфекций, 2019)
On 27 September 2019, Lidiya Stepanovana Pronina, former Head of the Editorial and Publishing Department at the RusRAPI “Microbe”, turned eighty.